Factors defining a pacemaker region for synchrony in the hippocampus - Wittner, Lucia (Blackwell Science Inc, 2007)
Synchronous activities of neuronal populations are often initiated in a pacemaker region and spread to recruit other regions. Here we examine factors that define a pacemaker site. The CA3a region acts as the pacemaker for disinhibition induced synchrony in guinea pig hippocampal slices and CA3b is a follower region. We found CA3a pyramidal cells were more excitable and fired in bursts more frequently than CA3b cells. CA3a cells had more complex dendritic arbors than CA3b cells especially in zones targetted by recurrent synapses. The product of the density of pyramidal cell axon terminals and dendritic lengths in innervated zones predicted a higher recurrent synaptic connectivity in the CA3a than in the CA3b region. We show that some CA3a cells but few CA3b cells behave as pacemaker cells by firing early during population events and by recruiting follower cells to fire. With a greater excitability and enhanced synaptic connectivity these CA3a cells may also possess initiating functions for other hippocampal ensemble activities initiated in this region.